GRAFTING OF ACRYLONITRILE ONTO POTATO STARCH (PS) USING eERIC AMMONIUM NITRATE As INITIATOR - Khan, A Rasheed; Syed, Kausar Ali; Ahmed, Khalil; Ifrahim, A F K (Biological Sciences - PJSIR, 2001)
Graft copolymerization of acrylonitrile (AN) onto potato starch (PS) using eerie ammonium nitrate as initiator was accomplished. Before grafting starch was gelatinized in two ways; one is dispersing PS in water and other in aqueous butanol. The results show that PS gelatinized in aqueous iso-butanol facilitates the grafting of growing polymer chain of AN onto backbone slightly better than PS gelatinized in water. The effects of monomer, backbone and catalyst concentration on rate of conversion of monomer, rate of graft copolymerization, rate of homopolymerization, grafting efficiency and grafting rate are discussed in detail. The absorbency of saponified products of each sample was determined in distilled water, tap water and aqueous solution ofNa Cl and KCl and discussed thoroughly.